Electrical and electrochemical properties of triphenylene based lithium solvated electron solutions - Lunchev, Andrey V. (2018)
Conductivity and open circuit potentials of lithium solvated electron solutions (Li SESs) based on triphenylene (TRI) in tetrahydrofuran (THF) were studied. It was found that those solutions with Li:TRI ratio >0.5 demonstrate much higher conductivity comparing to naphthalene based Li SES of same concentration, which can be related to TRI π-stacking properties. Based on the values of open circuit voltage in a half-cell, the values of entropy and enthalpy change were calculated for the Li:TRI ratios of 2:1 and 4:1. The value of ΔS for Li4.0 (TRI) (THF)123 is higher than the one for naphthalene based Li SES with Li:PAH ratio = 1:1. The obtained values are much higher than those for solid state electrodes used in lithium ion batteries. Based on quantum chemical modeling of lithium-triphenylene interactions, it was shown that the unusually high values of conductivity could be related to the formation of a dimeric conductive complex.